Epibiosis in decapod crustaceans by stalked barnacle Octolasmis lowei (Cirripedia: Poecilasmatidae) - Machado, Glauco B. de O.; Sanches, Fabio H. C. [UNESP]; Fortuna, Monique D. [UNESP]; Costa, Tânia Marcia [UNESP] (FapUNIFESP (SciELO), 2013)
Stalked barnacles Octolasmis lowei Darwin, 1851 are frequently found attached to decapod crustaceans. Their epibiotic association depends on many factors, which are mainly related to characteristics of the host's biology. This study evaluated the infestation and distribution of stalked barnacles in the branchial chambers of crabs, and analyzed the data with respect to the host's sex, maturity stage, molt cycle and size. The crab species Arenaeus cribrarius Lamarck, 1818, Callinectes danae Smith, 1869, Callinectes ornatus Ordway, 1863, Hepatus pudibundus Herbst, 1785, Libinia ferreirae Brito Capello, 1871, and Persephona punctata Linnaeus, 1758 were sampled and found to be infested by O. lowei. No juvenile crabs were infested. The prevalence of infestation by O. lowei was significantly different among C. danae, C. ornatus, and H. pudibundus males and females. All infested hosts were in the intermolt period. The mean size of infested crabs was larger than that observed for non-infested individuals. Internally, stalked barnacles were concentrated on the central gills or walls and floor of branchial chambers, suggesting that these gills provide more favorable conditions for the settlement and development of these epibionts. These results highlight the relationship between epibiont infestation and host biology, as well as the role of decapod crustaceans as a suitable substrate for the development of stalked barnacle O. lowei. © 2013 Sociedade Brasileira de Zoologia All rights reserved.
Keywords: Brachyurans; Epibiont; Host biology; Infestation; Symbiosis